The new Day of Atonement: a Matthean typology - Moscicke, Hans (Wissenschaftliche Untersuchungen zum Neuen Testament, 2020)
B. Apocalyptic Yom Kippur Traditions -- I. The Book of Watchers (1 Enoch 1-36) -- II. 4Q180-181 -- III. The Book of Giants -- IV. The Apocalypse of Abraham -- C. Additional Yom Kippur Traditions in Second Temple Judaism -- I. The Book of Zechariah -- II. The Book of Jubilees -- III. 11QMelchizedek -- IV. Yom Kippur at Qumran -- V. Heavenly Ascents in the Yom Kippur Imaginaire -- D. Extra-Biblical Scapegoat Rituals in Second Temple Tradition -- E. Yom Kippur Christologies in the New Testament -- I. The Pauline Letters -- II. The Epistle to the Hebrews -- III. The Book of Revelation